A restricted Boltzmann machine based prostate tumor detection in MRI images - Jassim Kredi, Mohammad; Nori Farhan, Rabah (International Journal of Engineering and Technology, 2019)
Context: Prostate cancer is a common and malignant tumor. Thus, to improve the excellence of life of cancer person is the early diagnosis of prostate cancer. Prostate tumors are divided in terms of growth to: slow growth and often confined to the prostate gland and growing growth and often spread the prostate gland to other members which is the second most regular reason for malignancy in the world According to estimates and studies conducted by the World Health Organization. MRI uses medical imaging technology used on a scale It is widely evaluated for tumors, but the large amount of data produced by MRI can vary greatly. Thus manual detection will be a challenge.The Problem: The early diagnosis of prostate cancer plays a key role in prolonging the patient's life. as doctors are still human, and rely on factors such as the eye in the diagnosis and these factors do not avoid mistakes in addition to that The wrong diagnosis presents the patient to death, especially the description of inappropriate treatment or surgical intervention (tumor contact) or chemical radiation therapy for this reason completed the diagnosis leads to high accuracy diagnosis, accuracy Diagnosis assumes an imperative job in the fight against the disease. Regular re-diagnosis is important and necessary to ensure that patients survive and keep them away from the risk of disease. However, re-diagnosis and examination often consumes many financial expenses in this regard. This system is designed to assist radiologists in their practice Clinical.Approach: In this paper, the researcher is interested in focusing on the area of the prostate gland and detecting abnormal cases in the image. The proposed strategy relies on one of the deep learning algorithms Restricted Boltzmann Machine algorithm, and image processing techniques histogram equalization one of Contrast enhancement techniques, to enhance grayscale images It improves the differentiation of pictures by changing the qualities in a force picture so the histogram of the output image approximately matches a specified histogram and extract the features that help us to make the right decision in the process of diagnosis as well as to increase the efficiency of the system and obtain the highest accuracy in the results where the use of dataset images of the magnetic resonance of the prostate, which contains more than 1700 different images of 230 infected and was classified using an algorithm to non-tumor and tumor.Finding: The results of this study confirmed that this method works effectively. This method was applied to a database containing 1730 medical images. The accuracy of this method was 98.8439. To demonstrate the productivity of the proposed system, the images were entered into a normal neural network. Than Indicates the efficiency of our proposed system.Â Â Â